(untitled) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
: This article explores the importance of assessing listening skills in the classroom and offers a variety of strategies for teachers to evaluate their students’ auditory comprehension and communication abilities. It emphasizes that listening is a fundamental skill for academic success, influencing a student’s ability to absorb information, engage in discussions, and interact with others. The article outlines several methods of assessment, including comprehension questions, note-taking exercises, peer-to-peer listening activities, and technology-assisted tools